A novel approach to remote laboratories - Deniz, Derviş Z.; Bulancak, Atilla; Özcan, Gökhan (Institute of Electrical and Electronics Engineers Inc., 2003)
Remote laboratories are becoming widely accepted in universities for providing distance education and for augmenting traditional laboratories. There is a lot of interest in remote laboratories from pedagogical point of view. In this paper, a novel technique for establishing remote laboratories is presented. The technique used and tools developed are extendable for the provision of different laboratory applications. Central to the idea is an experimentation server designed using a core web technology called the "Web-Kernel" which provides a common access point for remote experiments. The server supports a number of analog/digital interface cards as well as allowing access to a number of modern laboratory instrumentation including oscilloscopes and signal generators. The web-kernel provides access to web sessions over the Internet from remote student workstations and allows fast, reliable and efficient development of applications. It is expected that the realistic facilities provided within the system will allow it to be used in engineering education. © 2003 IEEE.
33rd Annual Frontiers in Education, FIE 2003 -- 2003-11-05 through 2003-11-08 -- Westminster -- 114471
Keywords: Distance learning; Pedagogy; Remote laboratory; Web experiments